(untitled) (Horizontes de Enfermería, 2018)
This article is focused on the use of the game that helps to develop the gross psychomotricity in children from 4 to 5 years of the Initial Education Center "Tomas Sacoto". Set as general objective to determine the game as a methodological strategy for the development of gross psychomotricity by analyzing the deficiencies and techniques and strategies used with children; As well as the motor skills acquired up to this point of 4 to 5 years. The research was of a qualitative and quantitative type based on the socio-educational modality, because it integrates cultural, social and educational fields; Descriptive study to study the present reality of the game as a methodological strategy for gross psychomotor development in boys and girls, for which the inductive deductive method was used; And the field using instruments such as the survey of teachers of the initial 2 and observation sheets to the children of the institution concluded that teachers have broad knowledge and application of various games as teaching methodology, It is important to emphasize that continuous and up-to-date training and the improvement of their knowledge are necessary. The spaces for the effect of the games need more equipment and amplitude so that the games are made in a better way.